Governance for sustainable tourism: A review and directions for future research - Borges, Maria do Rosário (2015)
Over the past two decades there has been a growing interest in the topic of governance in the context of several domains of the social sciences. More recently, the growing attention given by investigators to governance and its implication for tourism development has raised several core questions. However, research is still fragmented and different interpretations of the governance concept might lead to multiple reflections. This paper aims to present and discuss some fundamental theoretical issues related to governance within the context of tourism, tourism destinations and sustainable development. Conceptualisation, dimension and scale of governance are presented based on a literature review. This approach will also be used to do a synthesis of the main methodologies that have been used so far for data collection and analysis in scientific studies within these fields. The paper argues that the concept of governance is multidimensional and that there are no standardized solutions to ensure success through a universal approach to governance. Private and public sector and other actors are being forced to promote synergies within the same geographical area of intervention in order to face global competition and governance arrangements can facilitate this. The review also reveals that there is still only limited systematic and comparable empirical evidence of the role of governance in sustainable tourism destinations. Finally, because governance might represent a new pattern of interaction between government, private sector and society to cope with old and new problems or to create new opportunities to develop a sustainable tourism, some pathways for future research on this topic are also identified.